Abortion our bodies, their lies, and the truths we use to win - Valenti, Jessica 1978- (Crown, 2024)
"In a stirring and succinct examination of post-Roe America, "one of the most successful and visible feminists of her generation" (The Washington Post) takes on what's become the country's most resonant political issue. In her most urgent book yet, New York Times bestselling author Jessica Valenti shines a light on the conservative assault on women's freedom, cutting through the misinformation and overwhelm to inform, engage, and enrage. From the attacks Americans know about to the ones anti-abortion lawmakers and groups are trying to hide, Valenti details the tactics and horrors that she's been painstakingly tracking in her acclaimed newsletter, Abortion, Every Day. Abortion gives voice to women's frustration and outrage in a moment when they're fed up with being talked over and diminished. And in an election year when abortion is dominating the national conversation, Valenti provides the language, facts, and context readers need to feel confident talking about the attacks on their bodies and freedom. Abortion is a handbook for the overwhelming majority of Americans who support abortion rights, whether they're seasoned activists or those just starting to learn. With the wit, expertise, and blunt moral clarity that's made her writing popular for decades, Valenti offers an essential manifesto in an urgent moment"--